Harmony in Learning: Integrating Technology and Tradition in English Pedagogy - Sugiarto, Eko (Lembaga Yasin AlSys, 2024)
This research explores harmony in English language learning by integrating technology and tradition in pedagogical approaches. Through literature studies, classroom observations, and interviews, this study found that harmony is achieved by balancing the use of modern technology, such as online platforms and applications, with traditional values in learning. The results showed that this integration enriches students' learning experience while maintaining local cultural values. This research provides insight into how English language teachers can create learning environments that combine technological advances with traditional heritage, providing the basis for the development of holistic learning strategies.